The Concept And Essence Of Social Protection Of The Population (Texas Journal of Multidisciplinary Studies, 2024)
In the modern developing world, issues related to the system of social protection of the population are becoming relevant, since market relations put society in a sociocultural dead end. This gives rise to the problem of forming an adequate system of social protection for the most vulnerable sections of society. Therefore, this article makes an attempt to reflect the content space and essence of social protection. It is shown that social protection is functionally an integral system, which is an independent social institution and occupies a crucial place in the system of state policy to improve the level of well-being of the entire population and the quality of life of vulnerable categories of citizens.